Alphaworld: the storm is coming - Pigdon, Keith (Oxford University Press Melbourne, 2004)
The storm is coming, dark clouds rolling in like a thick blanket across the sky. The air feels charged with anticipation, and a cool breeze begins to stir, rustling leaves and sending a shiver through the trees. Distant rumbles of thunder echo, growing louder, as flashes of lightning briefly illuminate the horizon. People hurriedly secure their belongings and seek shelter, aware of the power nature is about to unleash. Raindrops begin to fall, gently at first, then intensifying into a heavy downpour. The world is transformed, with the storm bringing both chaos and a sense of renewal, reminding us of the raw forces of nature that shape our environment.